Atherosclerosis in rheumatoid arthtritis: the role of high-resolution B mode ultrasound in the measurement of the arterial intima-media thickness - G.M. Giuseppetti; A. Cerioni; M. Mangiacotti; F. Salaffi; M. Carotti; W. Grassi (PAGEPress Publications, 2011)
Background: Patients with rheumatoid arthritis (RA) have a reduced life expectancy and high cardiovascular morbidity and mortality as compared to the general population. A number of possible factors for the atherogenesis in this disease have been described, such as homocysteine, altered serum levels of selected lipopotroteins and treatment. Recent findigs indicate that the systemic inflammation may contribute to the development of atherosclerosis and confer an additional risk for cardiovascular death among patients with RA. The aim of our study was to evaluate the ability of high resolution Bmode ultrasoud and color Doppler to assess the existence of subclinical atherosclerosis in RA patients, measuring the intima- media thickness (IMT) and resistence index of the common carotid arteries. Methods: Carotid IMT and carotid plaque were measured using high-resolution B-mode ultrasound in 40 patients with RA and 40 age- and sex-matched healthy persons. We used color Doppler ultrasound to assess vascular damage of the common carotid arteries and the resistence index (RI) was determined by analysis of the spectral waveforms. Serum total cholesterol, trygliceridies, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, rheumatoid factor, body mass index (BMI), visual analogue scale (VAS) were determined in patients and controls. C-reactive protein (CRP) and the DAS28 were used to measure systemic inflammation. Results: Common carotid IMT were significantly higher (p=0.0009) in RA patients (0.83 ± 0.23) compared with controls (0.66 ± 0.22). In RA patients common carotid IMT was significantly correlated with serum total cholesterol (p=0.0008), low-density lipoprotein cholesterol (p=0.006), trygliceridies (p=0.042), age (p=0.031) and disease duration (p=0.019). No significant correlation was found with clinical and laboratory parameters reflecting disease activity. The prevalence of plaques was higher in RA patients compared with controls (25% vs 12.5%). There was no significant difference in color Doppler findings, and in particular in RI, between patients and controls. Conclusions: Our results confirm an accelerated atherosclerosis, as shown by increased common carotid IMT, in patients with RA compared with controls and it is related mainly to lipid levels. High-resolution B-mode ultrasound may be considered a promising, sensitive and non invasive tool for assessing the existence of subclinical atherosclerosis in RA patients.